2005
DOI: 10.1080/01431160512331299261
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal characterization of the spatial distribution of ulexite in a Bolivian salt flat

Abstract: Understanding spatial patterns is a critical and under-explored aspect of remote sensing. This paper describes how multifractal theory can be applied to characterize these heterogeneous patterns in remotely sensed data as well as to determine the operational scale. An example based on the characterization of ulexite distribution on the world's largest salt flat (10 000 km 2 ), located in Bolivia, using a binarized Landsat Thematic Mapper (TM) 4/7 ratio image, is used to describe the step-by-step procedure. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Moreover, the multifractal analysis gives a description of several physical properties of the observed signal such as the internal entropy, the anisotropy and the correlation among data. Indeed, multifractal analysis has been applied to signal data in several research fields such as solar flare X-ray emissions (McAteer et al 2007) soil science (Posadas et al 2003(Posadas et al , 2005, neurology (Yu et al 2001;Latka et al 2002) and cardiology (Ivanov et al 1999;Byalovskii et al 2005) among others. Hence, the objective of this work was to test the feasibility of using the multispectral light reflectance of plants, supported by conventional and wavelet-based multifractal analyses of the reflectance signal, for detecting R. solanacearum infection in potato crops, aiming at developing a practical field monitoring method for the spatial assessment of the health condition of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the multifractal analysis gives a description of several physical properties of the observed signal such as the internal entropy, the anisotropy and the correlation among data. Indeed, multifractal analysis has been applied to signal data in several research fields such as solar flare X-ray emissions (McAteer et al 2007) soil science (Posadas et al 2003(Posadas et al , 2005, neurology (Yu et al 2001;Latka et al 2002) and cardiology (Ivanov et al 1999;Byalovskii et al 2005) among others. Hence, the objective of this work was to test the feasibility of using the multispectral light reflectance of plants, supported by conventional and wavelet-based multifractal analyses of the reflectance signal, for detecting R. solanacearum infection in potato crops, aiming at developing a practical field monitoring method for the spatial assessment of the health condition of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…These two observations corroborate that generalized dimensions D q can provide an indicator of data heterogeneity degree, since their values would converge to a constant faster in images where pore distributions were less heterogeneous. Furthermore, Posadas et al (2005) have shown that homogeneous multifractal distributions have a narrow concave f(α)-spectra, whereas the opposite is true for heterogeneous structures. Thus, the wider is the magnitude of change of f(α) around the value f(α(0)), the higher is the heterogeneity of analyzed structures.…”
Section: Determination Of Multifractals Parametersmentioning
confidence: 99%
“…For multifractal pore distributions, the spectrum can be represented by a curve with a wide range of values for α. This interval increases with the increase of the distribution heterogeneity (Posadas et al, 2005;Xie et al, 2010). Multifractals generalized dimensions D q of the q −th order (Hentschel and Procaccia, 1983) are defined as:…”
Section: Multifractal Modelmentioning
confidence: 99%
See 2 more Smart Citations